Application of DMAIC method in an industrial case study - Silva, Q. (2020)
Purpose. In the present work DMAIC methodology is implemented in a Portuguese enterprise. The main goal is to reduce the percentage of non-conformities in an injection molded part for the automotive industry, through the elimination of defects that appear after painting. Design/methodology/approach. The DMAIC method was adopted to find an optimal set of factors that reduce the existing non-conformities. Along the five DMAIC phases, different quality tools were implemented to identify the root causes of the problem and to develop an action plan to reduce defects and minimize the process variability. Findings. In the application of this method, teamwork and brainstorming were essential for satisfactory results in a short period of time. A key finding is that the analysis of the possible causes that gave rise to the problem must be carried out separately, in order to easily identify the changes that created a significant improvement in the process. Research limitations/implications. The project is not fully completed since some of the improvement actions are being implemented. Originality/value. This paper describes a practical application of DMAIC methodology that contributed to reduce part defects and improve the production process of a Portuguese company.